Control Strategies and Behavioural Changes in the Elimination of COVID-19 from India - Srishti S. Chatterjee; Rupsita Sahu; Ramesh Nagarajappa; Debasruti Naik (Institute of Medico-legal Publications Pvt Ltd, 2021)
The massive spread of the novel coronavirus and its associated disease COVID 19 as a pandemic aroundthe world has gripped the international community, crippled healthcare systems and raised enormous publichealth concerns. The universe attempts to restrict the virus until now have yielded little fruit because of thezoonotic transmission ability of the virus. Countless healthcare professionals have already become infectedwith the disease and dentists are considered to be especially vulnerable. This article reviews the origins ofthe virus, its modes of transmission, symptoms and the recommendation provided to the dentists to diagnoseand manage a patient confirmed/ suspected of COVID 19 in the dental office.